Understanding Barrett's columnar lined oesophagus from the patients' perspective: qualitative analysis of semistructured interviews with patients. Issue 3 (29th March 2011) - Griffiths, Helen; Davies, Ruth
Abstract : Objectives: To explore patients' views and perspectives on their experience of living with Barrett's columnar lined oesophagus (CLO) and being part of an endoscopic surveillance programme. Design: Qualitative semistructured interviews. Setting: District General Hospital. Subjects: 22 men with diagnosis of Barrett's CLO between the ages of 50 and 70 years. Results: All subjects had received some information about Barrett's CLO and had a heightened awareness of the cancer risk. However, many had misinterpreted or poorly assimilated the information and overall health literacy levels were low. From their stories a 'Model of Uncertainty' in Barrett's surveillance was developed as a focus for healthcare professionals to ensure that the service users' perspective is considered in future service development. Conclusion: Patients' assimilation of information should not be assumed by healthcare professionals but rather should be verified for individual patients. The model developed highlights the factors found to influence patients' knowledge and understanding of Barrett's CLO.